Effect of Online Classes on Dry Eye Disease in Children: A Hospital Based Survey: Doi: 10.36351/pjo.v37i4.1322 - Salimath, Sangameshwarayya; Sultana, Salma; Patil, Brijesh Appasaheb; Kulkarni, Kalpana R; Nyamagoudar, Shishir K. (Pakistan Journal of Ophthalmology, 2021)
Purpose: To determine the effect of online classes on dry eye disease in children. Study Design: Cross sectional study. Place and Duration of Study: Department of Ophthalmology HSK hospital, Navanagar, Bagalkot, India, from October 2020 to November 2020. Methods: A total of 454 students attending online classes between the ages of 3 – 18 years were selected. Questionnaire was presented which included name, age, sex, residence, duration of online studies and duration in hours per day along with the various signs and symptoms according to SPEED questionnaire. Statistical analysis was performed using the IBM SPSS version 17. Quantitative variables were presented as mean ± standard deviation, while qualitative data was presented as frequency and percentages and compared by chi square test. P-value of < 0.005 was considered as significant. Results: Of the 454 responses, 316 (69.6%) had symptoms of dry eye disease, of which 159 were girls and 157 boys. There was no significant difference between boys and girls. Children taking online classes for 2 – 3 hours and for 4 to 6 months duration were more affected by the dry eye disease. Based on severity of grading system, 246 (84.2%) had mild symptoms, 42 (9.3%) had moderate symptoms and 28 ([6.2%) had severe symptoms. One hundred and twenty children visited ophthalmologist and 28.5% had their treatment of dry eye started. Conclusion: Online classes have resulted in increase in the frequency of dry eye disease in children. Proper education about the usage of screen time and educating parents about early treatment is essential. Key Words: Dry eye disease, Symptoms, Headache, Online learning.